Inclusive practices in Kazakhstan: validating the teacher efficacy for inclusive practice scale for the local context - Butabayeva, L.; Sharma, U.; Forlin, Ch.; Abildina, S.; Ismagulova, S.; Nogaibayeva, G. (International Journal of Developmental Disabilities, 2025)
Since 2011, Kazakhstan has made positive advances towards establishing inclusive education. To monitor ongoing progress effectively, this research aimed to validate the Teaching Efficacy for Inclusive Practices scale as an evidence-based approach on which to enable further decisions. Validation processes confirmed reliability for use in Kazakhstan. Subsequent analysis of data from 6,186 teachers revealed fairly positive perceptions of personal efficacy for providing inclusive instruction, managing behaviour, and collaboration. The implications for maintaining and enhancing inclusive practices in Kazakhstan are discussed considering these findings. Specific emphasis is placed on the identified impact of experience and increased training on improving perceived teacher efficacy; issues associated with the perceived challenges of behaviour management; and how these relate to the Government’s focus on improvement and training through the introduction of the new ‘comfortable’ inclusive schools.
Keywords: Teacher efficacy; inclusive education; Kazakhstan; scale validation; inclusion